Dossier : Des femmes qui comptent Genre et participation sociale en Grèce et à Rome (Mètis, 2020)
How can we offer researchers methods and tools that will allow them to write a history of antiquity across sexual lines? Relying on the methodology developed by the Eurykleia research group, the papers of this dossier explore the social practices that make women visible, as well as those in which women's presence, though real, seems to be less visible. The contributions emphasize the role of different modalities and discursive practices in the processes of display, conservation and transmission of women's names, and shed light on the specific logic of each context: oracular lamellae from Dodona, honorific decrees, conditional endowments, and the treatises of Cicero. The essays challenge certain biases regarding women in antiquity (for example, the so-called "names of hetairai]," and propose a revised vision of social relations in Greece and Rome.